Distribution of Human Papilloma Virus (HPV) in Cervical Adenocarcinoma and Adenosquamous Carcinoma - Mastutik, Gondo; Rahniayu, Alphania; Kurniasari, Nila; Rahaju, Anny Setijo; Harjanto, Budi (Folia Medica Indonesiana, 2021)
Approximately 20-30% of all cervical cancer cases are adenocarcinoma and adenosquamous carcinoma. Around 70% of all of these types of cancer are related to infection of Human Papillomavirus (HPV). This study evaluated the distribution of HPV genotype in cervical adenocarcinoma and adenosquamous carcinoma. A cross-sectional study was conducted at the Department of Anatomic Pathology, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January to December 2015. The sample were 22 formalin-fixed paraffin-embedded (FFPE) of cervical adenocarcinoma tissues and adenosquamous carcinoma tissues. FFPE was used for DNA extraction and followed with HPV genotyping to detect 40 genotypes of HPV, including low risk (LR) and high risk (HR) HPV. The histopathological types of adenocarcinomas were adenocarcinoma NOS and mucinous adenocarcinoma, while the adenosquamous carcinoma types were adenosquamous carcinoma and adenosquamous carcinoma glassy. All of the specimens were infected by HPV. In cervical adenocarcinoma, the infection was by HPV 6, 11, 16, 18, 31, 45, 68B, and 72, and in adenosquamous carcinoma by HPV 6, 16, 18, 45, and 59. HPV 18 was predominant, which was found in 13/22 (59.1%) in adenocarcinoma and 19/22 (86.4%) in adenosquamous carcinoma. Single infection and multiple infections in adenocarcinoma were 13/22 (59.1%) and 9/22 (40.9%), while in adenosquamous carcinoma were 21/22 (95.5%) and 1/22 (4.5%) respectively. The most common HR HPVs found in this study were HPV 18, HPV 45, HPV 16 and LR HPV are HPV 11, HPV 6.